What physical performance characteristics are related with age categories of elite young soccer players? - Medeiros, A. I. A.; Andrade, A. D.; Kassiano, W.; Silva, M. J. C.; Cunha, R. D. N.; Jerônimo, F. L.; Da Silva, G. M.; de Moura Simim, M. A. (Journal of Physical Education and Sport, 2023)
Aims: The purpose of this study was to compare the physical performance among young elite soccer players from different age categories (i.e., U15, U17, and U20) in a broad spectrum of abilities (sprint, change of direction ability, jump, anaerobic and aerobic capabilities) and to explore the relationship between these physical performances. Method: One hundred twenty-two young Brazilian soccer players were analyzed. The relationship and differences were assessed between physical performance in repeated sprint ability (RSA), sprint 10 and 20 meters, Yo-Yo IR1 test, countermovement jump, and change of direction ability (COD). Results: In sprint 10-m performance, U17 players were worse performance than U15 and U20 players (p = <0.001) and for sprint 20-m performance U17 category was faster when compared with the other categories (p = 0.008). For COD ability, results were favorable for U20 players (U15: p = 0.001; U17: p = <0.001) and U15 has worse performance (U17: p = 0.018; U20: p = <0.001). Performance for RSA variables, U20 players had better performance (p = 0.001), followed by U17 and U15 players. Likewise, performance in Yo-Yo IR1 were better for U20 players (p = 0.001), followed by U17 and U15 players. Jump performance was higher for U20 players. For relationship between physical performance according to category was observed that the number of significant relationships progressively reduced with increasing age category. In summary, this study revealed that the physical attributes that discriminated different age categories were 20-m time, RSA, COD ability, and distance performed on the Yo-Yo IR1.